Answer:
f(0) = 3
Step-by-step explanation:
Step 1: Distribute
f(x) = -3x + 3
Step 2: Plug in
f(0) = -3(0) + 3
f(0) = 3
Answer:
Option 3
Step-by-step explanation:
we are given the graph of a parabola
with vertex at (0,-1) and symmetrical about y axis and also open up.
Hence the equation of the graph would be transformation of ![y=x^2](https://tex.z-dn.net/?f=y%3Dx%5E2)
by a vertical shift of 1 unit down.
So new equation after transformation would be
![y+1=x^2](https://tex.z-dn.net/?f=y%2B1%3Dx%5E2)
Or![y=x^2-1](https://tex.z-dn.net/?f=y%3Dx%5E2-1)
Hence option 3 is right choice.
Verify:
Put Solving the equation we get
![x^2=1](https://tex.z-dn.net/?f=x%5E2%3D1)
![x=±1](https://tex.z-dn.net/?f=x%3D%C2%B11)
In the graph x intercepts are the same as -1 and 1
Hence our answer is right.
Answer:
2nd is the correct answer for your question
Answer:
Step-by-step explanation:
During the first year, ABC's stock price starts at $100 and increases by 100%. This means that the amount by which the stock increased would be
100/100 × 100 = $100
The new price of the stock would be 100 + 100 = $200
During the second year, its stock price goes down 25% from its price at the end of the first year. This means that the amount by which the stock reduced is
25/100 × 200 = 0.25 × 200 = $50
Therefore, the price of the stock, in dollars, at the end of the second year is
200 - 50 = $150